2023
DOI: 10.1111/jocd.15860
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study evaluating the anti‐aging benefits of a CO2‐emitting facial mask

Abstract: Background Since 1936, injectable carboxytherapy has been used for the treatment of circulatory issues and lack of tissue trophism. In the last 25 years, it has been applied to aesthetic issues, especially those related to the signs and symptoms of skin aging. Presently, carboxytherapy is available as a combination of transcutaneous gels that produce CO2 with benefit for atrophic skin. Objective The objective of this study was to investigate the efficacy and safety of a topical carboxy mask on facial photoagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…More recently, treatments with carboxytherapy have been used to stimulate the growth of collagen and elastin, reduce fatty tissue, treat scars and striae, eliminate wrinkles, and solve many other skin problems. [34][35][36][37] Hodeib et al enrolled 20 patients with striae in their study. Each patient received one carboxytherapy treatment on the left side of the body and one PRP treatment on the right side of the body.…”
Section: Carboxytherapymentioning
confidence: 99%
“…More recently, treatments with carboxytherapy have been used to stimulate the growth of collagen and elastin, reduce fatty tissue, treat scars and striae, eliminate wrinkles, and solve many other skin problems. [34][35][36][37] Hodeib et al enrolled 20 patients with striae in their study. Each patient received one carboxytherapy treatment on the left side of the body and one PRP treatment on the right side of the body.…”
Section: Carboxytherapymentioning
confidence: 99%
“…Wrinkles and fine lines signify premature aging. There are also dark spots and facial elasticity issues [1]. Premature aging causes skin to dry and darken, and acne scars take longer to erase.…”
Section: Introductionmentioning
confidence: 99%
“…However, premature aging is concerning. Several reasons cause aging, including psychological stress, pollution, and smoking [8]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…This study was coordinated with prior studies that found PAHs (polycyclic aromatic hydrocarbons) attached to combustion nanoparticles, which cause facial pigmentation. This may explain why industrial or heavily polluted locations have more lentigines and melasma [10]. Another skin-damaging combustion is cigarette smoke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation